Temperature changes under demineralized dentin during polymerization of three resin-based restorative materials using QTH and LED units - Sayed-Mostafa Mousavinasab; Maryam Khoroushi; Mohammadreza Moharreri; Mohammad Atai (Korean Academy of Conservative Dentistry, 2014)
Objectives Light-curing of resin-based materials (RBMs) increases the pulp chamber temperature, with detrimental effects on the vital pulp. This in vitro study compared the temperature rise under demineralized human tooth dentin during light-curing and the degrees of conversion (DCs) of three different RBMs using quartz tungsten halogen (QTH) and light-emitting diode (LED) units (LCUs). Materials and Methods Demineralized and non-demineralized dentin disks were prepared from 120 extracted human mandibular molars. The temperature rise under the dentin disks (n = 12) during the light-curing of three RBMs, i.e. an Ormocer-based composite resin (Ceram. X, Dentsply DeTrey), a low-shrinkage silorane-based composite (Filtek P90, 3M ESPE), and a giomer (Beautifil II, Shofu GmbH), was measured with a K-type thermocouple wire. The DCs of the materials were investigated using Fourier transform infrared spectroscopy. Results The temperature rise under the demineralized dentin disks was higher than that under the non-demineralized dentin disks during the polymerization of all restorative materials (p < 0.05). Filtek P90 induced higher temperature rise during polymerization than Ceram.X and Beautifil II under demineralized dentin (p < 0.05). The temperature rise under demineralized dentin during Filtek P90 polymerization exceeded the threshold value (5.5℃), with no significant differences between the DCs of the test materials (p > 0.05). Conclusions Although there were no significant differences in the DCs, the temperature rise under demineralized dentin disks for the silorane-based composite was higher than that for dimethacrylate-based restorative materials, particularly with QTH LCU.